Hyperbaric oxygen therapy for a pediatric electrical burn: A case report - Laura Marín; Graciela Fioravanti; Elisabet Cristaldo; Carlos Emilio Sereday; Oscar Merbilhaá; Mercedes Portas (Elsevier, 2020)
Contact electrical burns are more severe than others forms of contact burn injury. We present a 2- year-old case of electric injury admitted 48 h after injury treated with Hyperbaric Oxygen Therapy (HBOT) at 1.45 ATA ≈ 100%O2 like adjuvant therapy. She had thumb necrosis of right hand with 0.2% burn (0.1% type AB and 0.1% type B). After 6 sessions of HBOT, the amputation was limited to necrotic distal phalanx. This is a report of a successful limitation of amputation using escharotomy, skin flap and HBOT as therapeutic approach in a low voltage pediatric electrical burn.